2014
DOI: 10.1021/jp509427x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Dependence of Butyl Nitrate Formation in the Reaction of Butylperoxy Radicals with Nitrogen Oxide

Abstract: The yield of 1- and 2-butyl nitrates in the gas-phase reactions of NO with n-C4H9O2 and sec-C4H9O2, obtained from the reaction of F atoms with n-butane in the presence of O2, was determined over the pressure range of 100-600 Torr at 298 K using a high-pressure turbulent flow reactor coupled with a chemical ionization quadrupole mass spectrometer. The yield of butyl nitrates was found to increase linearly with pressure from about 3% at 100 Torr to about 8% at 600 Torr. The results obtained are compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This mechanism proceeds following destabilization of the ROONO moiety. In some cases, the nascent radicals do not separate but rather reform an activated RONO 2 complex, which then undergoes collisional stabilization to form the nitrate. As such, the yield will depend on the lifetime of the complex. This general mechanism is consistent with findings that alkyl nitrate yields tend to increase with the size of molecule and decrease with increasing temperature .…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism proceeds following destabilization of the ROONO moiety. In some cases, the nascent radicals do not separate but rather reform an activated RONO 2 complex, which then undergoes collisional stabilization to form the nitrate. As such, the yield will depend on the lifetime of the complex. This general mechanism is consistent with findings that alkyl nitrate yields tend to increase with the size of molecule and decrease with increasing temperature .…”
Section: Resultsmentioning
confidence: 99%
“…38 In more recent work, Butkovskaya et al suggested that a weakly bound adduct leads to both the formation of NO 2 and butyl nitrate although the structure was not optimized. 32 The identification of the vdW complex and the transition state leading to the organic nitrate in this study permits the quantification of the isoprene organic nitrate yield because the product distribution is acutely sensitive to the vdW energy relative to the barriers leading to NO 2 and RONO 2 .…”
Section: Results and Discussion (I) Isoprene Organic Nitrate Yieldsmentioning
confidence: 99%
“…Significantly, this species is common to both trajectories, and its identification here helps to rationalize the behavior of excited peroxynitrites, as will be discussed below. At this stage, the vdW complex may fragment completely using 4.2 kcal/mol of energy to generate the alkoxy radical and NO 2 , or the NO 2 may rotate so that the nitrogen faces the alkoxy radical to produce the organic nitrate with a concomitant release of energy, as discussed by Butkovskaya et al 32 The latter process possesses a minute barrier relative to complete vdW dissociation. This is consistent with the results of Zhang and co-workers, 13 which have indicated that the barrier to organic nitrate formation must be less than alkoxy radical production in order to observe increased alkoxy radical production at higher temperatures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations